Refining the phenotypical and mutational spectrum of Taybi‐Linder syndrome. Issue 6 (2nd June 2016) - Putoux, A.; Alqahtani, A.; Pinson, L.; Paulussen, A.D.C.; Michel, J.; Besson, A.; Mazoyer, S.; Borg, I.; Nampoothiri, S.; Vasiljevic, A.; Uwineza, A.; Boggio, D.; et al.
Abstract : Abstract : Taybi‐Linder syndrome (TALS, OMIM 210710) is a rare autosomal recessive disorder belonging to the group of microcephalic osteodysplastic primordial dwarfisms (MOPD). This syndrome is characterized by short stature, skeletal anomalies, severe microcephaly with brain malformations and facial dysmorphism, and is caused by mutations in RNU4ATAC . RNU4ATAC is transcribed into a non‐coding small nuclear RNA which is a critical component of the minor spliceosome. We report here four foetuses and four unrelated patients with RNU4ATAC mutations. We provide antenatal descriptions of this rare syndrome including unusual features found in two twin foetuses with compound heterozygosity for two rare mutations who presented with mild intrauterine growth retardation and atypical dysmorphic facial features. We also carried out a literature review of the patients described up to now with RNU4ATAC mutations, affected either with TALS or Roifman syndrome, a recently described allelic disorder.